The practicality of interleukin-6 in prognosis of blunt chest trauma in Korea: a retrospective study - Jeong Woo Oh; Tae Yeon Lee; Minjeong Chae (Journal of Trauma and Injury)
Purpose There are many studies on the practicality of interleukin-6 (IL-6) as a prognostic predictor in patients with multiple severe traumas. However, few studies focus on the practicality of IL-6 in patients with chest trauma. So, this study investigated whether IL-6 is effective as a prognostic factor in patients with blunt chest trauma. Methods A total of 44 blunt chest trauma patients who visited the regional trauma center from July to December 2021 were included in this retrospective study. Blood IL-6 levels were measured immediately after emergency room admittance (IL-6 E) and 24 hours after trauma (IL-6 24). To determine whether IL-6 levels can predict the clinical course and prognosis of patients with blunt chest trauma, the correlation between IL-6 (IL-6 E and IL-6 24) and the trauma score system, Injury Severity Score, Thoracic Trauma Severity Score, and Pulmonary Contusion Score, intensive care unit (ICU) stay period, and total hospitalization period were analyzed. Results IL-6 E showed a good correlation with Injury Severity Score (P=0.505), Thoracic Trauma Severity Score (P=0.597), Pulmonary Contusion Score (P=0.493), ICU stay period (P=0.762), and total hospitalization period (P=0.662). However, IL-6 24 had a relatively low correlation compared to IL-6 E. Therefore, IL-6 E showed useful results for predicting the prognosis of patients with blunt chest trauma. Conclusions Early plasma IL-6 levels (IL-6 E) can predict the injury severity of blunt chest trauma, length of ICU stay, and total hospitalization period.